2016
DOI: 10.1039/c6ra05672e
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties and photoactivity of monolayer MoS2/fullerene van der Waals heterostructures

Abstract: van der Waals (vdW) heterostructures have attracted immense interest recently due to their unusual properties and new phenomena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 64 publications
3
18
0
Order By: Relevance
“…The band gap of the MoS 2 /fullerene vdW heterostructure was smaller than that of monolayer MoS 2 , and thus, the visible‐light absorption and photoinduced electron transfer can be enhanced. Furthermore, the amount of charge transfer at interface induced by vdW interactions was found to be dependent on the size of the fullerene …”
Section: Hybrids Of Fullerene and Transition‐metal Disulfidesmentioning
confidence: 99%
“…The band gap of the MoS 2 /fullerene vdW heterostructure was smaller than that of monolayer MoS 2 , and thus, the visible‐light absorption and photoinduced electron transfer can be enhanced. Furthermore, the amount of charge transfer at interface induced by vdW interactions was found to be dependent on the size of the fullerene …”
Section: Hybrids Of Fullerene and Transition‐metal Disulfidesmentioning
confidence: 99%
“…Huang and co-workers have employed firstprinciples calculations based on DFT to understand the effects of vdW interactions on the charge transfer, the electronic structure, and photoactivity of MoS 2 /fullerene (C 60 , C 26 , and C 20 ) heterostructures. [133] It was found that the fullerene molecules can act as sensitizers when coupled with the MoS 2 nanostructures, which can improve photocatalytic activity. MoS 2 / fullerene monolayer heterostructures have smaller bandgaps of 1.75, 0.41, and 0.85 eV, compared to the pristine MoS 2 monolayers thus extending their absorption spectrum in the visible region.…”
Section: Metal Chalcogenides-functionalized Fullerenementioning
confidence: 99%
“…Fullerenes are known as single oxygen sensitizers to the electron acceptor–donor and have been used in photocatalysis . In photocatalytic systems, fullerene can create a space potential difference to enrich the separation and migration of the photogenerated charge carriers, as well as tuning the band gap . The amount of charge transfer in WS 2 /fullerenes and MoS 2 /fullerene (C 60 , C 26 , and C 20 ) heterostructures was found to depend on the nature of the fullerene.…”
Section: Recent Progress In the Design Of Semiconductor Photocatalystmentioning
confidence: 99%
“…In photocatalytic systems, fullerene can create a space potential difference to enrich the separation and migration of the photogenerated charge carriers, as well as tuning the band gap . The amount of charge transfer in WS 2 /fullerenes and MoS 2 /fullerene (C 60 , C 26 , and C 20 ) heterostructures was found to depend on the nature of the fullerene. In addition, a type‐II staggered band alignment, which was formed in the MoS2/C20 and WS2/fullerenes heterostructures, contributed to the enriched photocatalytic performance and the reduced charge recombination.…”
Section: Recent Progress In the Design Of Semiconductor Photocatalystmentioning
confidence: 99%